Formulation, adsorption performance, and mechanical integrity of triamine grafted binder-based mesoporous silica pellets for CO2 capture - Wadi, Basil; Mahomed, Anisa; Bai, Yang; Osatiashtiani, Amin; Manovic, Vasilije; Nabavi, Seyed Ali (Elsevier, 2021)
This work explored formulation of mesoporous silicas pellets using a range of bentonite and colloidal silica (LUDOX), aiming to optimise the binder composition that minimises any deteriorating effects on adsorption performance, while provides an adequate mechanical integrity. Thermogravimetric analysis, scanning electron microscopy, and dynamic mechanical analysis were used to structurally characterise the pellets. Furtherer, CO2 adsorption isotherms of synthesised pellets, pre and post triamine grafting, were measured. Bentonite was found to be an effective single binder that forms mechanically strong pellets and retains up to 85% of CO2 capacity of the base adsorbent. At the presence of LUDOX, hardness of the pellets was lower, caused the largest decrease in CO2 capacity. Formulation with 25% bentonite was found to provide pellets with post triamine functionalisation CO2 capacity equivalent to powder SBA-15, at an amine efficiency of 0.41 mol CO2/mol, while minimising pore blockage and maintaining a compressive strength of 1.5 MPa.
Keywords: Adsorption; Carbon capture; Amine grafting; Bentonite binder; Pellet formation; SBA-15